Chrononutrition against Oxidative Stress in Aging. (18th June 2013) - Garrido, M.; Terrón, M. P.; Rodríguez, A. B.
Abstract : Free radicals and oxidative stress have been recognized as important factors in the biology of aging and in many age-associated degenerative diseases. Antioxidant systems deteriorate during aging. It is, thus, considered that one way to reduce the rate of aging and the risk of chronic disease is to avoid the formation of free radicals and reduce oxidative stress by strengthening antioxidant defences. Phytochemicals present in fruits, vegetables, grains, and other foodstuffs have been linked to reducing the risk of major oxidative stress-induced diseases. Some dietary components of foods possess biological activities which influence circadian rhythms in humans. Chrononutrition studies have shown that not only the content of food, but also the time of ingestion contributes to the natural functioning of the circadian system. Dietary interventions with antioxidant-enriched foods taking into account the principles of chrononutrition are of particular interest for the elderly since they may help amplify the already powerful benefits of phytochemicals as natural instruments with which to prevent or delay the onset of common age-related diseases.